Arachnoid cysts of the quadrigeminal cistern: Proposal of a therapeutic algorithm based on a systematic review of literature - Leopoldo Mandic Ferreira Furtado; João Victor de Souza Santos; Fábio Santos Esteves Júnior; Aieska Kellen Dantas dos Santos; José Aloysio da Costa Val Filho (Brazilian Society for Pediatric Neurosurgery, 2022)
Introduction: Although quadrigeminal arachnoid cysts (QACs) are infrequent malformations of the arachnoid space, which affect the quadrigeminal cistern, they have important clinical consequences, such as hydrocephalus and compressive symptoms. Moreover, there is much controversy on its surgical management; thus, it is important to determine the current state of the art regarding the best treatment modality. Objective: This study aimed to examine the effectiveness of different surgical approaches and revisit the anatomy of the quadrigeminal cistern. Methods: A systematic review of the literature was conducted considering studies published in the last 20 years regarding the natural course and treatment of QACs. Only English papers were selected, and case reports were excluded from the analysis. Results: We identified 286 articles, of which nine were selected for the qualitative analysis. Clinical presentations of QACs included mental disorientation, bladder incontinence, dysphagia, quadriplegia, ataxia, and nocturnal headaches, which were dependent on the cyst size, and a spontaneous resolution was not described. A microsurgical technique via a supracerebellar infratentorial approach and fenestration to the third ventricle and ventricular endoscopic third ventriculostomy were the main techniques, which were performed depending on the anatomical features and presence of hydrocephalus. Shunt placement was associated with high rates of complications and recurrence. Conclusion: Despite the lack of solid evidence on the treatment of QACs, mainly due to their rarity, an endoscopic approach with ventricle cystostomy has been indicated as the more effective surgical technique.